Search for scalar bottom quarks and third-generation leptoquarks in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; et al. (Elsevier B.V., 2010)
We report the results of a search for pair production of scalar bottom quarks ((b) over bar (1)) and scalar third-generation leptoquarks (LQ(3)) in 5.2 fb(-1) of p (p) over bar collisions at the D0 experiment of the Fermilab Tevatron Collider. Scalar bottom quarks are assumed to decay to a neutralino ((chi) over bar (1)(0)) and a b quark, and we set 95% C.L. lower limits on their production in the (m((b) over bar1), m((chi) over bar 10)) mass plane such as m((b) over bar1) > 247 GeV for m(<(chi)over) (bar>10) = 0 and m((chi) over bar 10) > 110 GeV for 160 m(<(b) over bar1) < 200 GeV. The leptoquarks are assumed to decay to a tau neutrino and a b quark, and we set a 95% C.L. lower limit of 247 GeV on the mass of a charge-1/3 third-generation scalar leptoquark. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Supersymmetry; Leptoquarks; Third generation